PENGEMBANGAN MODEL PENENTUAN HARGA PRODUK - , AINUR KOMARIAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Price determines company profit. A company profit comes from the difference between revenue and overall cost to produce companyâs products. Revenue is the number of product units sold multiplied by the price. Thus, the price must be carefully considered. Factors considered in determining price are the costs and the value of intangibles, such as quality and brand. Quality which means superiority or advantages of a product, has positive effect on price, so does the brand. The research aims to develop mathematical models of product pricing by considering the cost, quality, and brand. The data used in this study are three primary data and twenty secondary data. The data is in the form of product price structure consisting production cost, value of quality, and value of brand. Production costs are calculated from the direct production cost, indirect production costs, and general expenses. Based on the information of production costs and sales volume, the internal rate of return analysis is carried out in order to obtain a reasonable price. Reasonable price is the price at minimum rate of return. The difference between fair price and the actual price is the intangible value of the product. Furthermore, value of quality and brand are determined from the intangible value, using the method of AHP based on the factor weights that have been set by the company. This price modeling using six common forms are sorted according to the complexity of the model. The model consists of two types, i.e. linear and nonlinear model, each with interaction and without interaction between variables. The simplest model involves three parameters, while the most complex model consists of sixteen parameters. The parameters are determined is by minimizing the sum of squared distance. The assesment criterion of the model is evaluated based on the sum of squared distance criterion (SSres), coefficient of determination (Adjusted R2), AIC score (Akaike Information Criterion), predictive capability, and the number of parameters involved. The research developed six mathematical pricing models which determine the product price with three variables (cost, quality and brand). All variables involved including price, have been normalized using the direct production costs. These six models produce highest SSres of 7,935